PERAN MIKORIZA ARBUSKULA DAN BAKTERI Pseudomonas fluorescens DALAM MENINGKATKAN SERAPAN P DAN PERTUMBUHAN TANAMAN JAGUNG PADA ANDISOL - Mohammad Kafid Musafa; Luqman Qurata Luqman Qurata Aini; Budi Prasetya (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2015)
Phosphorus that is absorbed by Al and Fe in Andisols makes it not available to plants. One of efforts to improve P availability in Andisols is application of agent containing phosphate biological solution. P. fluorescens bacteria have ability to dissolve P because it can produce organic acid that can absorb Al and Fe so that P can be available to plants. Mycorrhiza Arbuscular (MA) are fungi that have access to the source of P-organic by colonizing plant roots. The purpose of this study was to explore the role of MA and Pseudomonas fluorescens bacteria in increasing P uptake by maize grown in an Andisol. The results showed that the inoculation of P.fluorescens bacteria Â and MA increased P uptake by 24% and improved maize growth Â by 27.59%.